The peculiarities of surgical service of locally advanced breast cancer after neoadjuvant systemic treatment - O. L. Petrenko (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2015)
Patients with locally advanced (T2-4N0-3M0) breast cancer, receiving neoadjuvant systemic treatment with the following application of surgical treatment stage (radical mastectomy or conservative surgery) were selected from the data base. The data of the first cancer register in the Russian Federation, disposing the data base for more than 5000 patients with breast cancer were analyzed in this work. Consistent with the primary goal of the work the information about 286 patients with locally advanced breast cancer (clinical stages IIB-IIB), receiving neoadjuvant systemic treatment with the following application of surgical treatment stage (radical mastectomy or conservative surgery), was obtained from the date base. The follow up period is from 2 to 10 years. The estimation of application efficiency of neoadjuvant chemotherapy, hormonal treatment and target therapy was done. The basic clinical, pathomorphological and biological factors (HER2, ER, PR, degree of malignancy), decisive for planning of relevant neoadjuvant treatment, enabling to customize medical disposal for a patient and contributing to the increase of comprehensive treatment, rising of general and relapse free survival of patients with locally advanced breast cancer, who underwent breast-conserving surgeries.